Pengaruh Nilai Pelanggan terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan Aplikasi Bima+ Tri - Aditya, Cindy; Lestari, Retno Budi (MDP Student Conference, 2025)
This study aims to analyse the influence of customer value on customer loyalty with customer satisfaction as an intervening variable for Bima+ Tri users. This research uses quantitative methods, with nonprobability sampling techniques namely purposive sampling involving 140 respondents who are Bima+ Tri users. Data analysis includes validity test, reliability test, correlation coefficient test, coefficient of determination, simple and multiple regression analysis, significance test (t and F test), path analysis and sobel test using SPSS Statistics 26 software. The results showed that customer value have a positive and significant effect on customer satisfaction, customer value and customer satisfaction have a positive and significant effect on customer loyalty. Moreover, customer satisfaction successfully mediates the relationship between customer value and customer loyalty.